Changes in ganglion cell physiology during retinal degeneration influence excitability by prosthetic electrodes. (23rd February 2016) - Cho, Alice; Ratliff, Charles; Sampath, Alapakkam; Weiland, James
Abstract: Objective. Here we investigate ganglion cell physiology in healthy and degenerating retina to test its influence on threshold to electrical stimulation. Approach. Age-related Macular Degeneration and Retinitis Pigmentosa cause blindness via outer retinal degeneration. Inner retinal pathways that transmit visual information to the central brain remain intact, so direct electrical stimulation from prosthetic devices offers the possibility for visual restoration. Since inner retinal physiology changes during degeneration, we characterize physiological properties and responses to electrical stimulation in retinal ganglion cells (RGCs) of both wild type mice and the rd10 mouse model of retinal degeneration. Main results. Our aggregate results support previous observations that elevated thresholds characterize diseased retinas. However, a physiology-driven classification scheme reveals distinct sub-populations of ganglion cells with thresholds either normal or strongly elevated compared to wild-type. When these populations are combined, only a weakly elevated threshold with large variance is observed. The cells with normal threshold are more depolarized at rest and exhibit periodic oscillations. Significance. During degeneration, physiological changes in RGCs affect the threshold stimulation currents required to evoke action potentials.